Failure of Added Dietary Gluten to Induce Small Intestinal Histopathological Changes in Patients with Watery Diarrhea and Lymphocytic Colitis - Hugh James Freeman (Canadian Journal of Gastroenterology)
Lymphocytic colitis is a form of microscopic colitis usually characterized by watery diarrhea and often associated with biopsy-defined celiac disease. Two patients with lymphocytic colitis and normal small intestinal biopsies who were administered 40 g of added dietary gluten for four consecutive weeks are presented. Small intestinal biopsies from multiple sites in the proximal small bowel were done after three and four weeks to determine whether pathological changes in latent celiac disease could be induced in these patients with a high gluten-containing diet. In addition, colorectal biopsies were done to determine whether the colitis was sensitive to oral gluten. No alterations in the small intestinal biopsies were detected in either patient and no changes occurred in colitis severity. Although microscopic forms of colitis have been linked to celiac disease, this study indicates that lymphocytic colitis is a heterogeneous clinicopathological disorder that, in some patients, is independent of any gluten-induced intestinal pathological changes.